Listen, You are Writing! Speeding up Online Spelling with a Dynamic Auditory BCI - Schreuder, Martijn; Rost, Thomas; Tangermann, Michael (Frontiers in Neuroscience, 2011)
Representing an intuitive spelling interface for Brain-Computer Interfaces (BCI) in the auditory domain is not straightforward. In consequence, all existing approaches based on event-related potentials (ERP) rely at least partially on a visual representation of the interface. This online study introduces an auditory spelling interface that eliminates the necessity for such a visualization. In up to two sessions, a group of healthy subjects (N=21) was asked to use a text entry application, utilizing the spatial cues of the AMUSE paradigm (Auditory Multiclass Spatial ERP). The speller relies on the auditory sense both for stimulation and the core feedback. Without prior BCI experience, 76% of the participants were able to write a full sentence during the first session. By exploiting the advantages of a newly introduced dynamic stopping method, a maximum writing speed of 1.41 characters/minute (7.55 bits/minute) could be reached during the second session (average: .94 char/min, 5.26 bits/min). For the first time, the presented work shows that an auditory BCI can reach performances similar to state-of-the-art visual BCIs based on covert attention. These results represent an important step towards a purely auditory BCI.